Robert Frost and the “Eye Reader” - Jeremy Pomeroy (Anglica. An International Journal of English Studies)
One salient feature of Robert Frost’s aesthetics was his sharp differentiation of the visual from the audile imagination. Frost (a former schoolteacher) had noticed the difference between visual and audile/phonetic readers, and considered the eye reader to be a ‘bad’ reader. The article examines those features of Frost’s own poetic practice which would have led him to consider the eye reader a bad reader, as well as the sorts of prosodic content an eye reader may be prone to miss. Having examined Frost’s aesthetic objections to the eye reader, the question is then posed: does Frost ever treat the “eye reader,” or oral versus visual predilections, thematically in his artistic writings?